Estágio vivencial em oficina de criatividade: contribuições para a formação do psicólogo - Rosmaninho, Marta Tolaini (2015)
This thesis aims to understand, in a phenomenological approach and from the alumni point of view, the contributions that the experiential stage brings to the formation of the psychologist and to the professional practice. Semi-open interviews were held with four psychologists, who attended the experiential Creativity Workshop before graduation in Psychology and are graduated between two and five years ago. The interviews analysis followed the methodological proposals of phenomenology, supported by concepts presented by Merleau- Ponty. The analysis made it possible to understand that experiential Creativity Workshop provided an opportunity to expand the understanding of self and other, which favored the self knowledge of the psychologists. The learning of personal and relational nature reflected in the professional practice in Psychology